Pengaruh Kompensasi, Lingkungan Kerja, dan Disiplin Kerja terhadap Kinerja Karyawan pada Pengadilan Negeri Semarang - Ali Maskur; Via Yunita (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to determine and explain the influence of compensation, work environment and work discipline on employee performance at the Semarang District Court. This research uses primary and secondary data, and a sample collection technique using the Random Sampling method. Data was obtained through questionnaires from Semarang District Court employees to serve as an example for this research.The tests carried out in this research include validity tests, reliability tests, model tests, t tests and f tests. The results of this research show that the partial and stimulant variables of compensation, work environment and work discipline influence employee performance. The aim of this research is to determine the effect of work environment compensation and work discipline on employee performance.